2019
DOI: 10.1128/jvi.00659-19
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Costimulation Is Required for Development of Herpetic Stromal Keratitis but Does Not Prevent Establishment of Latency

Abstract: Corneal infection with herpes simplex virus 1 (HSV-1) leads to infection of trigeminal ganglia (TG), typically followed by the establishment of latency in the infected neurons. When latency is disrupted, the virus reactivates and migrates back to the cornea, where it restimulates the immune response, leading to lesions in a disease called herpetic stromal keratitis (HSK). HSK requires T cell activation, as in the absence of T cells there is no disease. We decided to determine if CD28 costimulation of T cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…These stressors not only suppress the immune system, but they also correlate with a loss of control of viral latency. This comes in the form of increased viral genomic DNA within the TG and a modest production and release of infectious virus (14,(165)(166)(167)(168)(169). Together, these data suggest that loss of viral control is a direct effect of immunosuppression.…”
Section: Adaptive Immunitymentioning
confidence: 90%
See 1 more Smart Citation
“…These stressors not only suppress the immune system, but they also correlate with a loss of control of viral latency. This comes in the form of increased viral genomic DNA within the TG and a modest production and release of infectious virus (14,(165)(166)(167)(168)(169). Together, these data suggest that loss of viral control is a direct effect of immunosuppression.…”
Section: Adaptive Immunitymentioning
confidence: 90%
“…B-cell deficiency during early infection can lead to viral dissemination to the brain, encephalitis and mortality ( 179 , 180 ). Serum antibodies are effective at controlling early viral replication of highly pathogenic HSV-1 strains like McKrae or SC16 ( 167 ). While serum antibodies have not been tested in less pathogenic models of disease, recent studies have shown how maternal antibodies prevent disease and morbidity in neonatal HSV infections ( 181 , 182 ), which illustrates a potential role that circulating antibodies play in the prevention of disseminated disease.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…CXCL10 is a ligand for the chemokine receptor CXCR3, which is highly expressed on activated T cells and is associated with recruitment of T cells to sites of inflammation. Downregulation of CXCL10 is a major indicator of impaired T cell migration to the site of inflammation ( 59 ). This could be further explained based on the enhanced T cell exhaustion (PD1) in TG of knockout mice in our study, which in turn interferes with T cell activation and function, as we have shown previously ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were reactivated from latency as previously described [21,22]. Briefly, the eyes of all latently infected mice were examined for corneal opacity prior to UV-B irradiation, and only animals with clear corneas were used, and mice with residual corneal disease from the primary infection are removed from the study.…”
Section: Uv-b Irradiation and Virus Reactivationmentioning
confidence: 99%
“…Stromal opacification was rated on a scale of from 0 to 4, where 0 indicates clear stroma, 1 indicates mild stromal opacification, 2 indicates moderate opacity with discernible iris features, 3 indicates dense opacity with the loss of defined iris detail except pupil margins, and four indicates total opacity with no posterior view. Corneal neovascularization was evaluated as described previously [21,22] using a scale of from 0 to 8, where each of the four quadrants of the eye is evaluated for the density of vessels that have grown into them. Periocular disease was measured in a masked fashion on a semiquantitative scale as previously described [39].…”
Section: Clinical Evaluationmentioning
confidence: 99%